Interest-Rate Volatility in Emerging Markets - Edwards, Sebastian; Susmel, Raul (The Review of Economics and Statistics, 2003)
We use high-frequency interest-rate data for a group of Latin American and Asian countries to analyze the behavior of volatility through time. We focus on volatility comovements across countries. Our analysis relies on univariate and bivariate switching volatility models. We compare the results from the switching models with those from rolling-standard-deviation models. We argue that the switching models are superior. Our results indicate that high-volatility episodes are, in general, short-lived, lasting from 2 to 7 weeks. We also find some evidence of interest-rate volatility comovements across countries.